Impact of APOL1 Genetic Variants on HIV-1 Infection and Disease Progression - An, Ping; Kirk, Gregory D.; Limou, Sophie; Binns-Roemer, Elizabeth; Kopp, Jeffrey B.; Winkler, Cheryl A. (Frontiers in Immunology, 2019)
Apolipoprotein L1 (APOL1) has broad innate immune functions and has been shown to restrict HIV replication in vitro by multiple mechanisms. Coding variants in APOL1 are strongly associated with HIV-associated nephropathy (HIVAN) in persons with untreated HIV infection; however, the mechanism by which APOL1 variant protein potentiates renal injury in the presence of high viral load is not resolved. Little is known about the association of APOL1 genotypes with HIV viral load, HIV acquisition, or progression to AIDS. We assessed the role of APOL1 coding variants on HIV-1 acquisition using the conditional logistic regression test, on viral load using the t test or ANOVA, and on progression to AIDS using Cox proportional hazards models among African Americans enrolled in the ALIVE HIV natural history cohort (n = 775). APOL1 variants were not associated with susceptibility to HIV-1 acquisition by comparing genotype frequencies between HIV-1 positive and exposed or at-risk HIV-1 uninfected groups (recessive model,12.8% versus 12.5%, respectively; OR 1.02, 95% CI 0.62-1.70). Similar null results were observed for dominant and additive models. APOL1 variants were not associated with HIV-1 viral load or with risk of progression to AIDS (Relative hazards (RH) 1.33, 95% CI 0.30-5.89 and 0.96, 95% CI 0.49-1.88, for recessive and additive models, respectively). In summary, we found no evidence that APOL1 variants are associated with host susceptibility to HIV-1 acquisition, set-point HIV-1 viral load or time to incident AIDS. These results suggest that APOL1 variants are unlikely to influence HIV infection or progression among individuals of African ancestry.